Digital Forensic-Ready Voting Model - Muyambo, Edmore; Baror, Stacey; Makura, Sheunesu (The Indonesian Journal of Computer Science, 2025)
The increasing digitalization of elections through internet-based voting (e-voting) systems introduces both opportunities for enhanced accessibility and threats to electoral integrity. Existing electronic voting systems often lack built-in forensic capabilities necessary to detect, preserve, and prove incidents of vote rigging or cyber manipulation. This paper proposes a Digital Forensic-Ready Voting Model (DFRVM) that integrates forensic-by-design principles, blockchain technology, and legal admissibility frameworks to ensure accountability, transparency, and verifiability in the electoral process. The model emphasizes proactive evidence collection, real-time monitoring, and tamper-evident audit trails to strengthen post-election dispute resolution.